Reduplicated Words Are Easier to Learn. Issue 4 (1st October 2016) - Ota, Mitsuhiko; Skarabela, Barbora
ABSTRACT: Infants' disposition to learn repetitions in the input structure has been demonstrated in pattern generalization (e.g., learning the pattern ABB from the token ledidi ). This study tested whether a repetition advantage can also be found in lexical learning (i.e., learning the word lele vs. ledi ). Twenty-four English-learning infants (mean age: 18.5 months) were exposed to novel word-object mappings involving either a reduplicated CVCV word (e.g., neenee ) or a nonreduplicated CVCV word (e.g, bolay ). Infants were more adept at learning word-object mappings with a reduplicated word than with a nonreduplicated word. A follow-up corpus analysis of infant-directed speech showed that this preference could not be attributed to the frequency patterns of reduplicated words or syllables in the linguistic input. These findings indicate that an experience-independent bias toward repeated elements plays an important role not only in pattern generalization but also in word learning.